Formulation Development of Tofacitinib Niosomes Using Design of Experiments - Lalitha, K.; Kusuma, M.P. (International Journal of Pharmaceutical Investigation, 2025)
Background Tofacitinib Citrate (TCB) is a selective Janus kinase inhibitor approved by the USFDA for the treatment of Rheumatoid arthritis. However, TCB faces extensive first pass metabolism and causes GI trouble on oral administration. To overcome these adverse effects of orally administered TCB, topical delivery can be a suitable alternative. Objectives The present research study aims to determine the process variables that affect the incorporation of TCB into niosomes by employing Box-Behnken Design (BBD) to finally produce an optimized TCB-Niosomes (TN), that could improve drug delivery to arthritic tissues and incorporating it in to hydrogel system to prepare TCB niogel. Materials and Methods Niosomes were prepared using Ethanol injection method. The critical material attributes and process parameters and their effect on product quality variables were assessed and optimized using BBD and a hydrogel was prepared with optimized TN and thus, has effectively trapped TCB. In vitro release properties of the TCB-loaded niosomes were studied and the anti-inflammatory effectiveness of these nanostructures was evaluated using an adjuvant-induced arthritis rat model. Results Optimized niosomes have particle size of 167±8.7 nm, PDI 0.2±0.04 and %EE 80.2±3.1. ZP of optimized TN was -32±2.1 indicating a stable preparation. In vitro drug release study for TCB niosomes, performed using dialysis bag method has shown an improvement compared to saturated drug solution and it followed korsmeyer peppas model (R2=0.9511) and Quasi-Fickian diffusion (n<0.4). In vivo studies revealed the improved efficiency of TCB niogel over conventional TCB gel with significant reduction in paw volume and arthritic score. Conclusion Our findings demonstrated that TCB niosomes can target inflamed tissues when administered topically in a niogel system and thereby, a promising and effective delivery of TCB that could offer safer and more efficient treatment to RA.
Keywords: Box-Behnken design; Niosomes; Rheumatoid arthritis; Tofacitinib citrate; Topical delivery